REVITALISASI MUTU FISIOLOGIS BENIH SEMANGKA (CITRULLUS LANATUS L.) MELALUI SEED PRIMING MENGGUNAKAN AIR KELAPA - Santika, Putri; Alvioneta, Novaria Rheina; Muhklisin, Ilham (Bajang Institute, 2025)
The decline in physiological quality of expired watermelon seeds poses a serious challenge in horticultural cultivation. This study aimed to evaluate the effectiveness of seed priming using young coconut water on the viability and vigor of both expired and non-expired watermelon seeds. The experiment was arranged in a factorial Completely Randomized Design (CRD) with two factors: coconut water concentrations (0%, 30%, 50%, and 70%) and seed age (one-year expired and non-expired), each with three replications. Observed parameters included germination rate, maximum growth potential, germination speed, and uniformity. The results showed that soaking in 50% coconut water for 4 hours produced the best outcomes across all parameters for both expired and non-expired seeds. Germination rate of expired seeds increased from 78% to 93.3%, and maximum growth potential, growth speed, as well as growth uniformity improved significantly. These findings indicate that coconut water at an optimal concentration functions effectively as a biopriming agent in revitalizing the physiological quality of expired watermelon seeds.